Lower lung-volume level induces lower vertical center of mass position and alters swimming kinematics during front-crawl swimming - Washino, S.; Murai, A.; Mankyu, H.; Ogita, F.; Kanehisa, H.; Yoshitake, Y. (Journal of Biomechanics, 2021)
We examined the impact of lung-volume levels on the vertical center of mass (CoM) position and kinematics during submaximal front-crawl swimming at constant velocity. Thirteen well-trained male swimmers (21.2 ± 2.0 years) swam the front-crawl for 15 m at a target velocity of 1.20 m s-1 while holding one of three lung-volume levels: maximal inspiration (MAX), maximal expiration (MIN), and intermediate between these (MID). The three-dimensional positions of 25 reflective markers attached to each participant`s body were recorded using an underwater motion capture system and then used to estimate the body`s CoM. The swimming velocity and the vertical CoM position relative to the water`s surface were calculated and averaged for one stroke cycle. Stroke rate, stroke length, kick rate, kick amplitude, kick velocity, and trunk inclination were also calculated for one stroke cycle. Swimming velocity was statistically comparable among the three different lung-volume levels (ICC [2,3] = 0.875). The vertical CoM position was significantly decreased with the lower lung-volume level (MAX: -0.152 ± 0.009 m, MID: -0.163 ± 0.009 m, MIN: -0.199 ± 0.007 m, P < 0.001). Stroke rate, kick rate, kick amplitude, kick velocity, and trunk inclination were significantly higher in MIN than in MAX and MID, whereas the stroke length was significantly lower (all P < 0.05). These results indicate that a lower lung-volume level during submaximal front-crawl swimming induces a lower vertical CoM position that is accompanied by a modulation of the swimming kinematics to overcome the increased drag arising from a larger projected frontal area.